3D printed alendronate-releasing poly(caprolactone) porous scaffolds enhance osteogenic differentiation and bone formation in rat tibial defects. (29th September 2016) - Kim, Sung Eun; Yun, Young-Pil; Shim, Kyu-Sik; Kim, Hak-Jun; Park, Kyeongsoon; Song, Hae-Ryong
Abstract: The aim of this study was to evaluate the in vitro osteogenic effects and in vivo new bone formation of three-dimensional (3D) printed alendronate (Aln)-releasing poly(caprolactone) (PCL) (Aln/PCL) scaffolds in rat tibial defect models. 3D printed Aln/PCL scaffolds were fabricated via layer-by-layer deposition. The fabricated Aln/PCL scaffolds had high porosity and an interconnected pore structure and showed sustained Aln release. In vitro studies showed that MG-63 cells seeded on the Aln/PCL scaffolds displayed increased alkaline phosphatase (ALP) activity and calcium content in a dose-dependent manner when compared with cell cultures in PCL scaffolds. In addition, in vivo animal studies and histologic evaluation showed that Aln/PCL scaffolds implanted in a rat tibial defect model markedly increased new bone formation and mineralized bone tissues in a dose-dependent manner compared to PCL-only scaffolds. Our results show that 3D printed Aln/PCL scaffolds are promising templates for bone tissue engineering applications.